Amniotic Membrane Transplantation in Ophthalmology - Demir, Tamer; Turgut, Burak; Çeliker, Ülkü (Fırat University, 2001)
Amniotic membrane have been used in various surgical procedures and especially in the 1980s it was subjected to many researches about treatment of ocular surface disorders. Recently, it has been used for the treatment of persistent epithelial defects, thermal and alkali burns, bullous keratopathy, surgical treatment of pterygium, corneal surface reconstruction, conjunctival reconstruction, excimer laser PRK, prevention of corneal vascularization, treatment of scleral and corneal perforations, bleb revision and glaucoma filtering surgery. Further studies are required to determine the usage of amniotic membrane in different indications.

Amniyotik membran çeşitli cerrahi prosedürlerde geniş bir kullanım alanı bulmuş ve özellikle 1980'li yıllarda oküler yüzey hastalıklarının tedavisinde çeşitli araştırmalara konu olmuştur. Son yıllarda persistan korneal epitel defektleri, termal ve alkali yanıklar, büllöz keratopati, pterjium cerrahisi, korneal yüzey rekonstruksiyonu, konjunktiva rekonstruksiyonu, excimer laser fotorefraktif keratektomi (PRK), korneal vaskülarizasyonun önlenmesi, skleral ve korneal perforasyonların tamiri, bleb revizyonu ve filtran cerrahide kullanılmaktadır. Amniyotik membranın farklı kullanım alanları gelecekte yapılacak klinik çalışmalarla ortaya konulacaktır.
OFTALMOLOJİDE AMNİYOTİK MEMBRAN